Company Valuation, Conflicts of Interest and Bankruptcy: A Case Study of Enron - Boodho, Roshan (2009)
Enron has been one of the biggest corporate failures in the history of the United States thereby affecting many institutions like banks, rating agencies and other stakeholders who invested in the equity of the energy giant. In a mere fifteen years of existence, Enron moved from a Houston energy based company to multinational enterprise with business activities the world over. The energy giant was trading traditional assets such as oil, gas and other energy products as well as unusual products such as internet bandwidth while gambling on weather conditions also generated a large portion of profits. Most studies have showed that accountants and auditors were responsible for the collapse of Enron. However, this research has uncovered a totally new aspect which is the role equity research analysts have played in the demise of Enron. The main findings of this research provide solid evidence that there existed conflicts of interest between rating agencies and the firms they rate. Analysts have deliberately positive valuation and investment recommendations while they overlooked publicly available information (such as the declining return on capital of Enron, reduction in free cash flows, sudden resignation of the Chief Executive Officer Jeff Skilling, restatement of profits, announcement of an investigation by the Securities and Exchange Commission, among other issues) clearly pictured the poor financial health of Enron. Analysts claimed that the underlying reason as to why they have maintained a positive recommendation for Enron throughout was due to ‘chinese walls’ which prevented them from obtaining information from investment bankers. However, this paper has proved that analysts intentionally issued biased valuations so as to obtain investment banking business from the firms they rate as such businesses are by far more profitable that the traditional company valuations and investment recommendation.